2013
DOI: 10.7592/ejhr2013.1.4.ruch
|View full text |Cite
|
Sign up to set email alerts
|

Humour styles, personality and psychological well-being: What’s humour got to do with it?

Abstract: The Humor Styles Questionnaire (HSQ) by Martin et al. (2003) measures four humour styles, namely affiliative, self-enhancing, aggressive and self-defeating. In contrast to former humour instruments, the HSQ has strong relations to various measures of psychological wellbeing. However, its incremental validity in relation to basic personality traits has not been sufficiently studied. Two studies analysed how much unique variance the HSQ contributed to predicting psychological well-being over and above personalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 30 publications
6
50
0
Order By: Relevance
“…Thus, the humor styles seem to have shifted away from their initial functions and now assess mainly adaptive vs. maladaptive uses of humor. This could, for example, explain why the aggressive humor style, which was initially conceptualized to aim at enhancing oneself, has been found to be either uncorrelated (e.g., Martin et al 2003;Ruch and Heintz 2013) or negatively correlated with self-esteem (e.g., Edwards and Martin 2010;Galloway 2010).…”
Section: Explanatory Approachesmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, the humor styles seem to have shifted away from their initial functions and now assess mainly adaptive vs. maladaptive uses of humor. This could, for example, explain why the aggressive humor style, which was initially conceptualized to aim at enhancing oneself, has been found to be either uncorrelated (e.g., Martin et al 2003;Ruch and Heintz 2013) or negatively correlated with self-esteem (e.g., Edwards and Martin 2010;Galloway 2010).…”
Section: Explanatory Approachesmentioning
confidence: 99%
“…Only a few studies so far have investigated the construct validity of the HSQ beyond its well-studied factorial validity (i.e., a replicable four-factor structure) and nomological network (i.e., correlations with other variables such as personality and well-being; but see Ruch and Heintz 2013). Martin et al (2003) reported in their construction article the relationships of the HSQ scales with four peer-reported HSQ items, which showed small to medium convergent validities and satisfying discriminant validities (except between the affiliative and selfenhancing humor styles).…”
Section: Construct Validity Of the Hsqmentioning
confidence: 99%
See 2 more Smart Citations
“…Although it has been shown that the study of the relationship between humor and (facets of subjective) well-being has several pitfalls (Heintz & Ruch, 2015;Ruch & Heintz, 2014), humor seems to have a potential to contribute to people's well-being. For example, correlational studies using (self-and peer-ratings of) character strengths consistently show robust positive relations in the upper range of the VIA strengths (e.g., Park, Peterson, & Seligman, 2004;Proyer, Ruch, and Buschor, 2013;Proyer, Gander, Wellenzohn, & Ruch, 2013).…”
Section: Introductionmentioning
confidence: 99%